Analysis Of Factors Affecting Construction Waste Reduction Using The Structural Equation Modeling Method - Francisco da Conceição Neves de Sousa; Sahadi; Ilham Poernomo; Nanta Sigit (International Journal of Technology and Education Research, 2026)
Construction waste consists of materials that are not desired directly or indirectly by the construction industry. This includes inert and non-biodegradable building materials such as sand, blocks, concrete, plaster, wood, iron, broken tiles, bricks, masonry, insulation, nails, electrical cables and reinforcement, as well as all residual materials (waste) originating from from the Construction Project Site.Data collection methods in this research were carried out by sending questionnaires via personal chat or via e-mail in the form of Google form to members of contractors, planning consultants, as well as construction supervision/management consultants and other parties operating in the territory of Indonesia, then the data The questionnaire was analyzed using Structural Equation Modeling (SEM) with the help of SPSS and AMOS programs.Factors that influence the reduction of construction waste include Contractual (X1) with an influence value of 0.154. Material Transportation (X2) with an influence value of 0.140. Material Storage (X4) with an influence value of 0.203. Use of Construction Materials (X6) with an influence value of 0.352. Professional Ethics (X7) with an influence value of 0.177. Managerial Action (X8) with an influence value of 0.329. Government Subsidies (X10) with an influence value of 0.337 and Government Regulatory Policy (X11) with an influence value of 0.294. Furthermore, factors that do not have a significant influence are Place Management and Planning (X3), Location Operations (X5) and Sustainability (X9). The most dominant factors influencing the reduction of construction waste include Use of Construction Materials (X6) with an influence value of 0.352 and government subsidies (X10) with an influence value of 0.337.